The Role of Audit Quality in the Relationship between ESG and Corporate Financial Performance - Rahmatika, Fina; Rahman, Taufikur (Journal of Accounting Inquiry, 2025)
Purpose: The purpose of this study is to determine how environmental, social, and governance performance affects financial performance and how audit quality is able to moderate the relationship between environmental, social, governance performance and financial performance in companies listed on ISSI. Methodology: The research method used is quantitative; the data in this study are secondary data accessed through the company's official website in the form of annual financial reports and sustainability reports. Sampling using the purposive sampling method and obtained a sample of 52 samples. The processing of this research data uses the EViews 12 application. Findings: The results of the study stated that environmental influences financial performance, social influences financial performance, independent board of commissioners influences financial performance, and audit committee influences financial performance. Institutional ownership influences financial performance. Audit quality as a moderating variable in the study can moderate the relationship between environmental and social factors and financial performance but failed to moderate the relationship between the independent board of commissioners, the audit committee, and institutional ownership and financial performance. Novelty: In this study, only the social aspects of GRI were used to assess social variables. and the use of the audit quality variable as a moderating variable.